Outcome in Childhood Stroke: Comparing Functional Outcome by Modified Rankin Scale with Neurological Outcome by Pediatric Stroke Outcome Measure - Aprasidze, Tatia; Shatirishvili, Teona; Oesch, Gabriela; Lomidze, Giorgi; Tatishvili, Nana (Journal of Pediatric Neurology, 2023)
Different scales are used as outcome predictors following arterial ischemic stroke (AIS) in children. Pediatric stroke outcome measure (PSOM) gives information about neurological deficits and function and modified Rankin scale (mRS) about functional outcome. Research examining the relationship between the two measures is scarce. The aim of this study is to correlate the two different scales and to get some information on the long course of outcomes according to these outcome measures. Sixty-one children with the diagnosis of AIS and normal neurodevelopment prior to stroke were investigated. Results of outcome measures (PSOM and mRS) from ≥ 2 years of follow-up were analyzed. Changes of neurological deficits (subcategories of PSOM) over time (discharge, 6 months, and ≥2 years) and prognostic impact on the outcome of the Pediatric National Institutes of Health Stroke Scale and etiology/risk factors are presented.Cramer's V with a coefficient of 0.836 (df-1) indicates a strong association between dichotomized total PSOM and mRS scores. The correlation between the total scales was strong (rho = 0.983, p < 0.001). The correlation coefficient was highest for sensorimotor (rho = 0.949, p < 0.001), then for language (rho = 0.464, p < 0.001) and cognitive (rho = 0.363, p = 0.004) subscales. PSOM scores improved at 6 months compared to the discharge state in sensorimotor (p<0.001) and language (p<0.026) domains, however, there was no statistically significant difference between PSOM scores at 6 months and >2 years follow-up. There was no improvement in cognitive PSOM scores during the follow-up period.There was a high concordance level between the two scales, illustrating that long-term neurological deficits after stroke are related to poor functional outcome. Significant improvement of sensorimotor and language function happened within the period from onset to 6 months of follow-up. Thus, early mobilization of appropriate rehabilitative therapy might improve the outcome. We conclude that both outcome classifications are applicable for assessing outcome after childhood AIS.
Keywords: outcome; pediatric stroke; functional outcome; PSOM; mRS